Balancing Dual Roles: Emotional Regulation and Telepressure Impacts on Public Employees’ Work-Family Balance - Arina Zahro Khoerunisa; Talitha Lintang Pertiwi (Universitas Ahmad Dahlan, 2026)
Work–family balance has become a critical issue in industrial and organizational psychology amid increasing workplace digitalization; however, research integrating individual internal resources and digital communication pressures remains limited, particularly within the context of Indonesian civil servants (Aparatur Sipil Negara, ASN). This study examined the effects of emotion regulation and workplace telepressure on work–family balance. A cross-sectional quantitative design was employed with 200 married civil servants aged 30–55 years, selected through purposive sampling. Data were collected via an online questionnaire and analyzed using multiple linear regression. The regression model was statistically significant, F(2, 197) = 209.37, p < .001, explaining 68% of the variance in work–family balance (R² = .68). Emotion regulation demonstrated a significant positive association with work–family balance, whereas workplace telepressure showed a significant negative association. These findings suggest that emotion regulation functions as a psychological resource that supports role balance, while persistent pressure to respond promptly to work-related messages may undermine boundaries between work and family domains. The study recommends implementing emotion regulation training (e.g., stress management and adaptive coping programs) and establishing organizational digital communication policies (e.g., response-time guidelines, designated “quiet hours,” and supervisory support for boundary management) to enhance work–family balance among civil servants in digitally mediated work environments.